Standardization of pre-sowing seed treatment with electric, magnetic, rhizobium and panchagavya on growth, yield and yield parameters of Radish (Raphanus sativus L.) variety Taj F1 - Prashant Kumar Rai; Guvvala Harikishan Reddy; Vaidurya Pratap Sahi (Annals of Agricultural Research, 2024)
The present study was carried out to determine the effect of ten doses of pre sowing seed treatment of electric, magnetic, rhizobium and panchagavya on Radish variety Taj F1 in randomized block design during Rabi 2023 in the Field Experimentation Centre, Department of Genetics and Plant Breeding, Sam Higginbottom University of Agriculture, Technology and Sciences, Naini, Prayagraj, Uttar Pradesh along with control. The results showed that all the pre-sowing seed treatments recorded significant variation for pre harvest and post-harvest parameters of the radish crop as compared to control. The treatment rhizobium@10% for10 hours (T8) significantly recorded the highest values for field emergence (93.73%), plant height (39.83cm), number of leaves (13.73), leaf length (16.46cm), leaf area (181.05cm), chlorophyll content (2.06mg/g), root length (23.51cm), root girth (4.78cm), fresh weight of root (124.77 gm), root yield per plot (11.83) and moisture content (95.97%) as compared with the other treatments while lowest were recorded in control (T0). This study helps to quest for new innovative green technologies for achieving maximum productivity has become a pressing priority in the current scenario.